Faktor yang Berhubungan dengan Gejala Sick Building Syndrome - Larasati, Deva Nindya; Wahyuningsih, Anik Setyo (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Sick Building Syndrome (SBS) is a syndrome caused by the work environment. SBS is stated as a health problem in the work environment which is related to poor indoor air quality. The Central Java Provincial Health Office building is in the city center so it is an environment prone to air pollution. The purpose of this study was to determine the factors that influence SBS symptoms in Central Java Provincial Health Office employees. Methods: This study uses an analytic study type with a cross-sectional approach. The sample in this study were 73 respondents. The sampling technique used purposive sampling technique. The instruments used were questionnaires and measurements. The data analysis used the chi square statistical test. Results: The results of this study showed that among the 73 respondents there was a relationship between age and SBS symptoms (p=0.020), there was a relationship between gender and SBS symptoms (p=0.010), there was a relationship between years of service and SBS symptoms (p=0.020 ), there was a relationship between room temperature and SBS symptoms (p=0.007), there was a relationship between the number of bacteria and SBS symptoms (p=0.004), there was no relationship between room air humidity and dust levels and SBS symptoms. Conclusion: Age, gender, length of service, and number of bacteria are factors associated with SBS symptoms. In an effort to reduce the risk of SBS symptoms, workers need to relax body muscles, optimize the use of AC, increase AC maintenance, turn off the AC for a moment and open windows periodically.